Application of CFRP Sheets Repair to an Existing Steel Girder End. (2017) - Miyashita, Takeshi; Garcia, David Galicia; Hidekuma, Yuya; Kobayashi, Akira; Kuroki, Kouji
Abstract: In recent years, a new method to repair corroded girder ends using CFRP sheets have been proposed. Since this is a new method, there are only a few cases where CFRP was used to repair steel bridges, and the data about its performance on real bridges is still scarce. Therefore, the aim of this study is to evaluate the CFRP repair method performance on a corroded steel girder end by verifying the strain reduction on this section. The stress reduction is evaluated from on-site loading tests and confirmed through a Finite Element Analysis (FEA).